From Tripitaka to Isan Phaya: On Common Characteristics of Existence - Sa-ngiamwibool, Amporn; Srinok, Somchai (Universitas Sanata Dharma, 2017)
Phaya, or a philosophical verse of local people in northeastern Thailand or locally called Isan whose culture is intimate to that of Lao Peopleâ€™s Democratic Republic, is believed to be influenced by Buddhist Dhamma. It is, therefore, interesting to analyze how the local Isan philosophers borrowed ideas from the source and composed this valuable cultural heritage, with a specific focus on the theme of common characteristics of existence, consisting of anicca (impermanence), dukkha (suffering) and anatta (non-self). 252 existing verses were explored with a focus on common characteristics of existence. The findings revealed that the essence of the verses was literally borrowed from the source, Tripitaka, and figuratively adjusted for literary purposes. Implications of this analysis reassure that phayas are a truly cultural and religious heritage for the two countries.Keywords: Tripitaka, Isan phaya, common characteristics of existenceÂ